Adherence to Antimalarial Drug Therapy among Vivax Malaria Patients in Northern Thailand (Journal of Health, Population and Nutrition, 2009)
Vivax malaria is a significant cause of morbidity due to malaria in northern Thailand, accounting for approximately 50% of all malaria cases. The objective of this study was to determine the behavioural factors associated with adherence to the standard 14-day course of chloroquine and primaquine, prescribed from malaria clinics, among patients with vivax malaria. A retrospective study was conducted among 206 patients living in Muang and Mae Sa Riang districts of Mae Hon Son province in northern Thailand. Data on adherence and potential behavioural factors relating to adherence were collected using a structured interviewer-administered questionnaire and supplemented with qualitative data from focus-group interviews. The results indicated that 76.21% of the 206 patients with vivax malaria did not complete the medication course. The adherence of the patients was associated with knowledge scores of malaria (adjusted odds ratio [AOR]=2.2, 95% confidence interval [CI] 1.1-4.5) and accessing drug prescription scores (AOR=5.6, 95% CI 2.13-15.3). Therefore, further effort is needed to educate patients with vivax malaria on knowledge of malaria and its treatment with simple health messages and encourage them to adhere to their treatment. Key words: Antimalarials; Chloroquine; Drug adherence; Drug therapy; Primaquine; Malaria; Retrospective studies; Vivax malaria; Thailand doi: 10.3329/jhpn.v27i1.3313 J Health Popul Nutr 2009 Feb;27(1):4-13